Shear behaviour of brick-mortar interface in CFRP retrofitted or repaired masonry - Luccioni, Bibiana Maria (2010)
There are many unreinforced masonry buildings all over the world. Many of them are located in seismic zones and are, therefore, susceptible to lateral forces caused by earthquakes. The transmission of these forces to the foundations is made through load bearing walls and depends on the shear strength and stiffness of masonry. In plane shear strength of load bearing masonry walls depends on many factors like the bricks and mortar strength and the way the wall is constructed. It is mainly due to shear strength of the brick-mortar interface given by the adhesion and by the friction caused by normal compression loads. Under severe seismic loads the ultimate strength capacity of the interface is achieved and the structure collapses. The results of an experimental program performed to study the shear behaviour of CFRP retrofitted and repaired masonry are presented in this paper. Increase of strength, ductility and stiffness due to the addition of CFRP laminas is specially analyzed. Specimens formed by three bricks and two mortar joints without reinforcement, retrofitted and repaired with CFRP laminas were tested under quasi-static and cyclic load. Additionally, the numerical study of the same specimens is presented. The specimens were modelled with 2D and 3D finite elements programs. Orthotropic plasticity models were used for bricks and mortar, including brick-mortar interfaces and CFRP laminas. Experimental results were used to calibrate the parameters of the material models and a numerical tool for the mechanical analysis of retrofitted or repaired masonry panels was developed. A parametric numerical study was also carried out with these numerical models in order to obtain the optimal dimensions and orientation of the reinforcing bands.